Routine Activities Theory? A Kindly Critique and a Pathway Forward - Steinmetz, Kevin F. (Victims & offenders, 2025)
Routine Activities Theory (RAT) is a mainstay of victimological theory. This analysis builds upon prior scholarship to critique RATs utility as a causal theory of victimization. This critique focuses on two primary concerns. First, the theory, as originally articulated, is vague regarding the kinds of social changes important in shaping routine activities, the routine activities that matter for producing crime and victimization, and the processes or mechanisms through which social changes produce variations in routine activities. Second, the theory includes both necessary and subjective criteria for establishing suitable targets and capable guardians, both of which introduce complications for the theory. The necessary elements are potentially tautological as they merely describe targets or guardianship while the perceptual render the theory indistinguishable from rational choice or deterrence theory. Despite these issues, theory provides an extraordinarily useful descriptive framework for understanding the dimensions of crime and victimization. As such, this analysis encourages scholars to avoid treating RAT as a standalone explanatory theory and, instead, revert to its original framing as an “approach.” This analysis then provides one example of how RAT, as an approach, can be useful for guiding victimological research and theorizing going forward.